2010
DOI: 10.1051/agro/2009010
|View full text |Cite
|
Sign up to set email alerts
|

Solid—liquid separation of animal slurry in theory and practice. A review

Abstract: -Animal slurry contains plant nutrients that are essential for crop production. However, intensive livestock production may lead to a surplus of plant nutrients on farms and, as a consequence, discharge or emission to the environment. In order to ensure that the slurry applied to fields matches the nutrient requirements of the crops, techniques have been developed to reduce the nutrient content of slurry by means of separation. This review discusses the separation technologies used for animal slurry treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
235
1
20

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(280 citation statements)
references
References 129 publications
(159 reference statements)
9
235
1
20
Order By: Relevance
“…This contrasting finding probably derives from the cattle manure in our study being in solid form prior to anaerobic digestion. Typically more total P is partitioned into the solid than liquid (slurry) fraction of manure (Hjorth et al, 2010), which was the substrate for the anaerobic digestion process in our study, rather than an animal manure slurry used by Vanden Nest et al (2015). The higher annual precipitation and temperature and the acidic soil in Belgium may have also contributed to differences with our study.…”
Section: Olsen-phosphorusmentioning
confidence: 72%
“…This contrasting finding probably derives from the cattle manure in our study being in solid form prior to anaerobic digestion. Typically more total P is partitioned into the solid than liquid (slurry) fraction of manure (Hjorth et al, 2010), which was the substrate for the anaerobic digestion process in our study, rather than an animal manure slurry used by Vanden Nest et al (2015). The higher annual precipitation and temperature and the acidic soil in Belgium may have also contributed to differences with our study.…”
Section: Olsen-phosphorusmentioning
confidence: 72%
“…This phenomenon would be caused by the enhanced formation and precipitation of calcium phosphate, magnesium phosphate, and/or struvite through mineralization of N, P, and Mg during (co-)digestion in combination with a substantial increase of the manure pH (Hjorth et al, 2010;Le Corre et al, 2009;Möller and Müller, 2012). As a comprehensive example, Güngor et al (2007) showed that 43% of the mineral P species in dairy manure were struvite and 57% more weakly bounded dicalcium phosphate (CaHPO4:2H2O), whereas 78% struvite and 22% hydroxylapatite (Ca5(PO4)3(OH)) were detected in the digested manure sample.…”
Section: Digestate and Animal Manurementioning
confidence: 99%
“…The solid-liquid separation of cattle slurry has been referred as a good solution for manure management at farm scale and with potential to reduce the environmental impact of cattle-slurry (Hjorth et al, 2010). The derived solid fraction is generally exported out of the farm and the derived liquid fraction (LF) can be used to substitute mineral N application since it contains a high amount of ammonium (NH 4 + ) (Villar & Guillaumes, 2010).…”
Section: Introductionmentioning
confidence: 99%